An fMRI study of nonverbally gifted reading disabled adults: has deficit compensation effected gifted potential? - Gilger, Jeffrey W.; Talavage, Thomas M.; Olulade, Olumide A. (Frontiers in Human Neuroscience, 2013)
Neuroscience has advanced our understanding of the neurological basis of reading disability. Yet, no functional imaging work has been reported on the twice-exceptional dyslexic: individuals exhibiting both nonverbal-giftedness and reading disability (RD). We compared groups of reading-disabled (RD), nonverbally-gifted (G), nonverbally-gifted-RD (GRD), and control (C) adults on validated word-rhyming and spatial visualization fMRI tasks, and standardized psychometric tests, to ascertain if the neurological functioning of GRD subjects was similar to that of typical RD or G subjects, or perhaps some unique RD subtype. Results demonstrate that GRD adults resemble non-gifted reading disabled (RD) adults in performance on paper-and-pencil reading, math and spatial tests, and in patterns of functional activation during rhyming and spatial processing. Data are consistent with what may be a shared etiology of reading disability and giftedness in GRD individuals that yields a lifespan interaction with reading compensation effects, modifying how their adult brain processes text and spatial stimuli.